2019
DOI: 10.1242/jcs.226886
|View full text |Cite
|
Sign up to set email alerts
|

Transcytosis maintains CFTR apical polarity in the face of constitutive and mutation-induced basolateral missorting

Abstract: Apical polarity of cystic fibrosis transmembrane conductance regulator (CFTR) is essential for solute and water transport in secretory epithelia and can be impaired in human diseases. Maintenance of apical polarity in the face of CFTR non-polarized delivery and inefficient apical retention of mutant CFTRs lacking PDZ-domain protein (NHERF1, also known as SLC9A3R1) interaction, remains enigmatic. Here, we show that basolateral CFTR delivery originates from biosynthetic (∼35%) and endocytic (∼65%) recycling miss… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 79 publications
(116 reference statements)
0
6
0
Order By: Relevance
“…To explore the relative localization of CFTR with apical and basolateral markers, we conducted a triple stain of CFTR with wheat germ agglutinin (WGA), another apical marker (55), and the Na ϩ /K ϩ -ATPase ( Fig. 4).…”
Section: Vx-809 Rearranges Cftr Nhe3 and Enac In Adpkd Cysts Relatimentioning
confidence: 99%
See 1 more Smart Citation
“…To explore the relative localization of CFTR with apical and basolateral markers, we conducted a triple stain of CFTR with wheat germ agglutinin (WGA), another apical marker (55), and the Na ϩ /K ϩ -ATPase ( Fig. 4).…”
Section: Vx-809 Rearranges Cftr Nhe3 and Enac In Adpkd Cysts Relatimentioning
confidence: 99%
“…Bidaud-Meynard et al (55) have demonstrated that in airway cells basolateral CFTR delivery occurs via both biosynthetic (ϳ35%) and endocytic (ϳ65%) pathways and that basolateral channels are retrieved via basolateral-to-apical transcytosis, enhancing CFTR apical expression by 2-fold and suppressing its degradation. Given that CFTR has been observed in the basolateral membranes of both secretory and absorptive epithelia, the observation that VX-809 increases the localization of CFTR at the basolateral membrane indicates that VX-809 increases the stability of WT CFTR at the basolateral membrane.…”
Section: Vx-809 Rearranges Cftr Nhe3 and Enac In Adpkd Cystsmentioning
confidence: 99%
“…The transition of CD13 from the adhesion to apical site is reminiscent of basolateral-to-apical transcytosis described for a few proteins 53,54 . CFTR was shown to undergo apical-transcytosis through a Rab11-independent mechanism involving EEA1 + vesicles, raising the possibility that CD13 may redistribute to the AMIS through a transcytosis-like pathway.…”
Section: Discussionmentioning
confidence: 86%
“…It is known that in secretory epithelia, newly processed CFTR first traffics to the basolateral membrane and then is transcytosed to the apical membrane. 61 Thus, it is not unusual to detect CFTR colocalization within the basolateral membrane. One can readily see that in del4 cholangiocytes, the colocalization of CFTR with the basolateral marker is reduced, likely contributing to cyst formation in a manner similar to that in ADPKD.…”
Section: Discussionmentioning
confidence: 99%